Windrose Based of Surface Wind Profiles Over a Decade at Soekarno – Hatta International Airport - Noor, Heri Azhari; Fachrurrozi, M.; Fitrianto, M. Agus (WARTA ARDHIA, 2024)
The study of surface wind characteristics in the airport area is needed to support flight operations in terms of safety and economy. Surface wind data is required during the aircraft take-off and landing phases. The information on surface wind characteristics is used for planning flight operations or the construction and expansion of an airport runway. Using the frequency distribution method, a description of the monthly surface wind pattern was obtained. The results in Soekarno-Hatta International Airport area over 10 years period showed that in January - April the surface wind direction is dominated from the west, May - September is dominated from the east. The months of October, November, and December are a transition from easterly to return to the west (dominated from the south and southwest). This is in line with the general pattern of Indonesia's climate which is influenced by the west monsoon and east monsoon phenomena.